MSP-Tool: A VBA-Based Software Tool for the Analysis of Multispecimen Paleointensity Data - Monster, Marilyn W. L.; de Groot, Lennart V.; Dekkers, Mark J. (Frontiers in Earth Science, 2015)
The multispecimen protocol (MSP) is a method to estimate the Earth’s magnetic field’s past strength from volcanic rocks or archeological materials. By reducing the amount of heating steps and aligning the specimens parallel to the applied field, thermochemical alteration and multi-domain effects are minimized. We present a new software tool, written for Microsoft Excel 2010 in Visual Basic for Applications (VBA), that evaluates paleointensity data acquired using this protocol. In addition to the three ratios (standard, fraction-corrected and domain-state-corrected) calculated following Dekkers and Böhnel (2006) and Fabian and Leonhardt (2010) and a number of other parameters proposed by Fabian and Leonhardt (2010), it also provides several reliability criteria. These include an alteration criterion, whether or not the linear regression intersects the y axis within the theoretically prescribed range, and two directional checks. Overprints and misalignment are detected by isolating the remaining natural remanent magnetization (NRM) and the partial thermoremanent magnetization (pTRM) gained and comparing their declinations and inclinations. The NRM remaining and pTRM gained are then used to calculate alignment-corrected multispecimen plots. Data are analyzed using bootstrap statistics. The program was tested on lava samples that were given a full TRM and that acquired their pTRMs at angles of 0, 15, 30 and 90° with respect to their NRMs. MSP-Tool adequately detected and largely corrected these artificial alignment errors.